Firm Competition and Cooperation with Norm-Based Preferences for Sustainability - Roman Inderst; Eftichios S. Sartzetakis; Anastasios Xepapadeas (The Journal of Industrial Economics, 2023)
We analyze firms' incentives to coordinate on the introduction of a sustainable product variant when consumers' preferences for sustainability depend on the perceived social norm, which in turn is shaped by average consumption behavior. We show that such preferences could lead to multiple equilibria. If the level of competition among potential adopters is very low and adoption of the sustainable variant allows them to sufficiently expand their aggregate market share, they will coordinate on introducing the sustainable variant when a lenient legal regime makes this feasible. If competition among them is intense and market expansion under the sustainable variant is very limited, coordination can forestall the adoption of the sustainable variant. Our analysis thus both confirms and qualifies the notion of a sustainability “first-mover disadvantage” as a justification for an agreement between competitors, which has gained traction in antitrust. We also provide empirical evidence for norm-based sustainability preferences.
Keywords: 330